2011
DOI: 10.4103/0972-2327.82802
|View full text |Cite
|
Sign up to set email alerts
|

A case of Spinocerebellar Ataxia from ethnic tribe of Assam

Abstract: Here we present the case of a 17-year-old girl belonging to an ethnic tribe (Bodo tribe) of Assam, presenting with bilateral cerebellar signs and with history suggestive of an autosomal dominant pattern of inheritance, who was found to have spinocerebellar ataxia 7 on genetic testing. This case throws light on the probability of more such cases in the multi-ethnic society of the North-Eastern Indian states, which are not studied or reported till date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…[51112] Almost all previously published studies suggest that there is a strong correlation of clinical presentation to CAG repeat counts. Some common undisputed genotype phenotype correlations are listed below.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[51112] Almost all previously published studies suggest that there is a strong correlation of clinical presentation to CAG repeat counts. Some common undisputed genotype phenotype correlations are listed below.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical and genetic profile of SCA7 is derived mostly from the Scandinavian studies[ 2 7 8 9 10 ] and a few recent Asian studies. [ 5 11 12 ] Almost all previously published studies suggest that there is a strong correlation of clinical presentation to CAG repeat counts. Some common undisputed genotype phenotype correlations are listed below.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent communication reported detection of rare SCA 7 from ethnic tribe of Assam. [45] In a recent study from Western India, Khadilkar et al . reported 14 consecutive index cases of SCA and found that SCA 2 (10/14) was the commonest.…”
Section: Introductionmentioning
confidence: 99%